Answer:
0
Step-by-step explanation:
This deals with simplification or other simple results.
Answer:
Honestly i dont even know
Step-by-step explanation:
(f∘g)(x) is equivalent to f(g(x)). We solve this problem just as we solve f(x). But since it asks us to find out f(g(x)), in f(x), each time we encounter x, we replace it with g(x).
In the above problem, f(x)=x+3.
Therefore, f(g(x))=g(x)+3.
⇒(f∘g)(x)=2x−7+3
⇒(f∘g)(x)=2x−4
Basically, write the g(x) equation where you see the x in the f(x) equation.
f∘g(x)=(g(x))+3 Replace g(x) with the equation
f∘g(x)=(2x−7)+3
f∘g(x)=2x−7+3 we just took away the parentheses
f∘g(x)=2x−4 Because the −7+3=4
This is it
g∘f(x) would be the other way around
g∘f(x)=2(x+3)−7
now you have to multiply what is inside parentheses by 2 because thats whats directly in front of them.
g∘f(x)=2x+6−7
Next, +6−7=−1
g∘f(x)=2x−1
Its a lts easier than you think!
Hope this helped
The derivative of inverse trigonometric identities follow<span> a set of rules. </span>
<span>For </span>arc cos<span> x, the </span>dy/dx is equal to -1/ square root of (1 - x2).
<span>In this case, we still have 1/2 x inside the angle quantity so we multiply the </span>dy/dx above with 1/2. Hence, y' = is -1<span>/ 2 square root of (1 - x2); x = 1, y' is infinity. this means the line is horizontal. The answer hence is y = 1.</span>
Answer:
10
Step-by-step explanation:
3(2x - 4) = 4(x + 2)
6x - 12 = 4x + 8
-4x -4x
2x - 12 = 8
+12 +12
2x/2 = 20/2
x = 10